Attempt at dendrochronological dating of the medieval gold-ore processing mill found in Stará Pazderna near Písek, South Bohemia - Pták, Martin; null, null; Stehlíková, Eva; Koppová, Eva; Fröhlich, Jiří; Šálková, Tereza; Jiřík, Jaroslav (Verlag Marie Leidorf, 2014)
The research of gold-ore processing mill situated on the right side of Otava river at Stará Pazderna was led by Jaroslav Kudrnáč in 1967. The mill was dated to between the second part of the 13th century and the beginning of the 14th century through the pottery found there. Dendrochronological analyses were carried out. Data were obtained for 15 of the 26 samples of wood taken from the well-preserved medieval goldore mill building. The mill was built in AD 1323. The species composition of the wood indicates intentional selection of Pinus sylvestris to build the foundation of the mill, whereas Quercus sp. was preferred for fixing stocks.
Pokus o dendrochronologické datování středověkého zlatorudného mlýna nalezeného ve Staré Pazderně u Písku, jižní Čechy
Keywords: dendrochronology, gold-ore processing mill, Stará Pazderna; dendrochronologie, zlatorudný mlýn, Stará Pazderna